Gastrointestinal helminths of Adélie penguins (Pygoscelis adeliae) from Antarctica - Diaz, Julia Inés; Fusaro, Bruno; Longarzo, Lucrecia; Coria, Néstor Rubén; Vidal, Virginia; D'Amico, Verónica; Barbosa, Andrés (Polar Research, 2016)
Knowledge about parasitic organisms in Antarctica is scarce and fragmentary. The study reported here adds to the knowledge of gastrointestinal parasites of the Adélie penguin (Pygoscelis adeliae) (Sphenisciformes), from 25 de Mayo/King George Island (South Shetlands), Bahia Esperanza (Hope Bay) and Avian Island (Antarctica). Thirty-five freshly dead specimens (20 chicks and 15 adults) were collected from December 2007 to December 2014 and examined for internal macroparasites. Three adult parasite species were found: one Cestoda, Parorchites zederi, and two Nematoda, Stegophorus macronectes and Tetrameres sp. Immature Tetrabothrius sp. were found in hosts from Avian Island. Helminth communities are known to be related to host feeding behaviours. Low parasite richness observed in Adélie penguins could be related to the stenophagic and pelagic diet of this host species, which feeds almost exclusively on krill. Keywords: Parorchites zederi; Stegophorus macronectes; Tetrameres sp.; parasites; ecosystem health.
Keywords: Antarktis; krill; parasitter; pingviner; plankton; zoologi; økosystemer

Parasites of the Antarctic toothfish (Dissostichus mawsoni Norman, 1937) (Perciformes, Nototheniidae) in the Pacific sector of the Antarctic - Gordeev, Ilya I; Sokolov, Sergey G (Polar Research, 2016)
The Antarctic toothfish (Dissostichus mawsoni Norman, 1937) is one of the main target species of commercial fisheries in the Antarctic. It is an endemic and is found along the shelf of Antarctica, as well as on the slopes of seamounts, underwater elevations and islands in the sub-Antarctic. It feeds on a variety of fish and cephalopods and can be an intermediate/paratenic host of some helminthes, whose final hosts are whales, seals, large rays and sharks. This article presents new data on toothfish infection in the Pacific sector of the Antarctic. Specimens were examined during commercial longline fishing in the Ross Sea and the Amundsen Sea in January–February 2013. Fourteen species of parasites were found using standard parasitological methods and genetic analysis. Keywords: Toothfish; parasites; Antarctic fisheries; CCAMLR; infection; Southern Ocean.
Keywords: Rosshavet; Sørishavet; fiskeri; infeksjon; parasitter; parasittologi